2021
DOI: 10.13037/ci.vol22n49.7426
|View full text |Cite
|
Sign up to set email alerts
|

Framing Analysis como Metodologia de Estudo para Estratégias de Legitimidade Institucional: o caso JBS S.A. após escândalos de corrupção

Abstract: O artigo volta-se ao universo da legitimidade social de organizações empresariais em tempos de crises a partir de um diálogo metodológico com a tradição da framing analysis. Busca-se identificar as estratégias de legitimação utilizadas pela empresa JBS S.A. nos anos de 2017 e 2018 em resposta aos danos à imagem causados por operações deflagradas pela Polícia Federal. São estudados 37 comunicados aos investidores e 62 notícias institucionais. Infere-se que as estratégias de ganho de legitimidade estão diretamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Furthermore, the results allow advancement in the understanding that the greater the individual’s ecological awareness, the lower their trust in morally transgressive brands. In our case study, the transgression happened during the production process of commercialized animal protein, as disclosed by “Operação Carne Fraca” (“Operation Weak Meat”), an investigation by the Brazilian Federal Police over malpractices in meat processing companies (Silva et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, the results allow advancement in the understanding that the greater the individual’s ecological awareness, the lower their trust in morally transgressive brands. In our case study, the transgression happened during the production process of commercialized animal protein, as disclosed by “Operação Carne Fraca” (“Operation Weak Meat”), an investigation by the Brazilian Federal Police over malpractices in meat processing companies (Silva et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, management plays a role in finding the best practices for sustainable production (Macht et al, 2020). Therefore, identifying sensitive issues has been crucial in formulating strategies to increase companies' credibility with the public (Silva et al, 2021). This article proposes to bring research closer to the daily needs of management, a demand identified by Macht et al (2020), which is the SDGs 12 and 15 explained by the UN proposed agenda (United Nations, 2015, p. 14).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations